Hubungan pola asuh dengan kejadian stunting pada anak usia 24-59 bulan - Listina, Febria; Maritasari, Dwi Yulia; Aziza, Nurul; Rukmana, Nova Mega; Agata, Annisa (Holistik Jurnal Kesehatan, 2025)
Background: Stunting is a condition in which toddlers have a length or height that is less when compared to age. The factor of bad parenting in the family is one of the causes of nutritional problems. A preliminary study conducted by researchers at the Sumber Arum village obtained data have a stunting toddler with a total of 41 children under five from the target number of 0-5 years as many as 267 and designated as 10 areas with locus stunting. Purpose: To relationship of parenting with the incidence of stunting in children aged 24-59 months. Method: Analytical research with a cross-sectional approach. The population in this study were toddlers aged 24-59 months totaling 108 people with a sampling technique using the Slovin formula. The sample in this study amounted to 85 respondents. Data analysis used univariate and bivariate chi square tests. Results: The relationship analysis using the chi square test, obtained a p-value of 0.000 (p<0.05), which means that there is a significant relationship between maternal parenting patterns and the incidence of stunting in Sumber Arum Village, Kotabumi I Health Center Working Area in 2023 and obtained OR amounting to 0.066 (95% CI 0.023-0.192) indicating that toddlers who receive parenting are 0.066 times the determining factor in the occurrence of stunting. Conclusion: There is a relationship between maternal parenting patterns and the incidence of stunting in children aged 24-59 months, indicated by the results of p-value = 0.000 and OR = 0.066. Suggestion: Further research can add to the experience and insight of science about stunting. In addition, it can use the same variables, but the respondent groups and characteristics are different.   Keywords: Parenting; Stunting; Toddlers.   Pendahuluan: Stunting adalah kondisi ketika balita memiliki panjang atau tinggi badan yang kurang jika dibandingkan dengan balita seumurannya. Faktor pola asuh yang tidak baik dalam keluarga merupakan salah satu penyebab timbulnya permasalahan gizi. Studi pendahuluan yang dilakukan peneliti di Desa Sumber Arum diperoleh data memiliki balita stunting dengan jumlah 41 balita dari jumlah sasaran anak usia 0-5 tahun sebanyak 267 dan ditetapkan sebagai 10 daerah dengan locus stunting. Tujuan: Untuk mengetahui hubungan pola asuh dengan kejadian stunting pada anak usia 24-59 bulan. Metode: Penelitian analitik dengan pendekatan cross-sectional. Populasi dalam penelitian ini adalah 108 balita berusia 24-59 bulan dengan teknik sampel menggunakan rumus slovin. Sampel dalam penelitian ini berjumlah 85 responden. Analisis data menggunakan univariat dan bivariat uji chi square. Hasil: Analisis menggunakan uji chi square diperoleh p-value sebesar 0.000 (p<0.05), berarti terdapat hubungan yang signifikan antara pola asuh ibu dengan kejadian stunting dan diperoleh OR sebesar 0.066 (95% CI 0.023-0.192) menunjukkan balita yang mendapat pengasuhan, 0.066 kali lipat dari faktor penentu terjadinya stunting. Simpulan: Ada hubungan pola asuh ibu dengan kejadian stunting pada anak usia 24-59 bulan, ditunjukkan dengan hasil p-value =0.000 dan OR =0.066. Saran: Penelitian selanjutnya dapat menambah pengalaman dan wawasan ilmu pengetahuan tentang stunting. Selain itu, dapat menggunakan variabel yang sama, tetapi kelompok responden dan karakteristik yang berbeda.   Kata Kunci: Balita; Pola Asuh; Stunting.